Assessing the Socio-economic Potential of Cashew Nut Farming in Rangamati, Bangladesh - Chakma, Amit; Chakma, Netui; Chakma, Omeek; Talukder, Eco; Rabbany, Md. Yeamin; Jamal, Samrina; Al Mahbub, Hossain; Ahmed, Rashed (MANDALIKA : Journal of Social Science, 2025)
The socioeconomic and environmental potential of cashew nut production in Bangladesh's Ranganati Hill District is examined in this study while emphasizing the crop's potential as a cash crop for rural development. With yields of 1.4 to 1.8 tons per hectare and net returns exceeding those of conventional crops, cashew farming—which was first promoted by the Department of Agricultural Extension and the Chittagong Hill Tracts Development Board—has proven very profitable. This study explores the socio-economic viability of cashew nut farming in Rangamati, Bangladesh, as a sustainable alternative for rural livelihoods. Despite advantageous agro-climatic conditions, the industry nevertheless confronts obstacles, including weak marketing infrastructure, insufficient financial facilities, and restricted availability of high-quality planting supplies. Sixty farmers participated in the research, which was carried out in eight Ranganati upazilas. It used primary and secondary data to examine the variables that affect cashew production, such as land types, seedling sources, cultivation expenses, and economic profitability. According to the findings, steep hills were the favoured land type, and 63% of farmers switched to cashew growing because it was profitable. Most farmers paid between 11.000 and 15.000 Taka a year for cultivation and obtained seedlings from the Upazila Agriculture Office (UAO). With domestic pricing between 500 and 600 BDT per kilogram and production costs between 300 and 350 BDT, cashew cultivation exhibits strong economic viability, resulting in a 95–100% profit margin. However, the sector's expansion is hampered by a lack of high-quality processing facilities and training. The research comes to the conclusion that cashew farming may greatly boost rural employment, poverty alleviation, and GDP development in Bangladesh with the right governmental support, infrastructural investment, and capacity building